The Myriad Legacies of 1917 A Year of War and Revolution - Abbenhuis, Maartje; Atkinson, Neill; Baird, Kingsley; Romano, Gail (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
XVII, 299 p. 20 illus., 14 illus. in color.